2011
DOI: 10.1063/1.3664731
|View full text |Cite
|
Sign up to set email alerts
|

Fighting the curse of dimensionality in first-principles semiclassical calculations: Non-local reference states for large number of dimensions

Abstract: Semiclassical methods face numerical challenges as the dimensionality of the system increases. In the general context of the theory of differential equations, this is known as the “curse of dimensionality.” In the present manuscript, we apply the recently-introduced multi-coherent states semiclassical initial value representation (MC-SC-IVR) approach to extend the applicability of first-principles semiclassical calculations. The proposed strategy involves the use of non-local coherent states with the goal of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
92
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(92 citation statements)
references
References 96 publications
0
92
0
Order By: Relevance
“…In the case of FFT, momenta and positions are expressed in their Fourier series representations, while AS is based on a time-dependent perturbation of the initial normal mode Hamiltonian, which is smoothly increasing in time until the true Hamiltonian is obtained. AS has been successfully applied even to the reactive abstraction of hydrogen in the Cl+CH 4 reaction 11 and to H 2 CO. 12 Also, impressive calculations of quantum vibrational energies using the Semiclassical Initial Value Representation of Miller were recently reported for H 2 CO. 13,14 Nevertheless, the application of these methods to highly vibrationally excited states remains practically an unsolved problem.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of FFT, momenta and positions are expressed in their Fourier series representations, while AS is based on a time-dependent perturbation of the initial normal mode Hamiltonian, which is smoothly increasing in time until the true Hamiltonian is obtained. AS has been successfully applied even to the reactive abstraction of hydrogen in the Cl+CH 4 reaction 11 and to H 2 CO. 12 Also, impressive calculations of quantum vibrational energies using the Semiclassical Initial Value Representation of Miller were recently reported for H 2 CO. 13,14 Nevertheless, the application of these methods to highly vibrationally excited states remains practically an unsolved problem.…”
Section: Introductionmentioning
confidence: 99%
“…In few words, the integration of eq (3) is reduced to a sum of trajectories starting from the convenient set of coherent state centers pictorially reported in Figure Figure 1. Single-well simulations 8,24,25 showed that the coherent state momenta do not need to be placed at an energy very close to the eigenvalues, because the Gaussian spreading of each coherent state is wide enough to include the peak energy shell 8,24 . The necessary quantum mechanical delocalization is provided by the presence of several coherent states on each well with energy both below and above the barrier.…”
mentioning
confidence: 99%
“…To better identify each spectral peak, we enforce the A 1 symmetry into our coherent states combination of eq (5) by doubling the number of coherent states. 8,23 The A 1 vibrational levels are highlighted in Figure Figure 2 allowing us to prove the presence of tunneling splittings of the order at least of a few wavenumbers. Considering that the barrier height for the are examples of the possibility to correctly detect a deep tunneling effect.…”
mentioning
confidence: 99%
See 2 more Smart Citations